THE ACCURACY AND PRECISION OF SMALL-SIZED MODERN WOOD SAMPLES ANALYZED AT THE CHRONOS 14CARBON-CYCLE FACILITY. Issue 2 (21st April 2023) - Haines, Heather A; Hiscock, William T; Palmer, Jonathan G; Turney, Chris S M; Thomas, Zoë A; Cadd, Haidee; Vohra, Juee; Marjo, Christopher E
ABSTRACT: Tree-ring series offer considerable potential for the development of environment-sensitive proxy records. However, with traditional increment cores, only small amounts of wood are often available from annual tree-ring sequences. For this reason, it is important to understand the reliability (and reproducibility) of radiocarbon measurements obtained from small-sized samples. Here we report the F 14 C results from the Chronos 14 Carbon-Cycle Facility of modern tropical Australian tree samples over a range of four graphite target sizes from the same rings. Our study shows that similar precision can be obtained from full-sized, half-sized, as well as small-sized graphite targets using standard pretreatment and analysis procedures. However, with a decline in sample size, there was an increase seen in the associated variance of the ages and the smallest target weights started showing a systematic bias. Wiggle-matching accuracy tests, comparing the Southern Hemisphere post-bomb atmospheric calibration curve to the different sample weight sequences, were all significant except for the 200 μgC graphite targets. Our results indicate that samples smaller than 350 μgC have limited accuracy and precision. Overall, reliable measurements of F 14 C sequences from tree-ring records across a range of sample sizes, with best results found using graphitized samples >350 μgC.